The Incidence and Economic Burden of In-Hospital Venous Thromboembolism in the United States - KÜÇÜKDURMAZ, FATİH; Shahi, Alisina; Chen, Antonia F.; Tan, Timothy L.; Maltenfort, Mitchell G.; Kucukdurmaz, Fatih; Parvizi, Javad (My University, 2017)
Background: Venous thromboembolism (VTE) is a potentially preventable and costly complication after total hip arthroplasty (THA) and total knee arthroplasty (TKA). The in-hospital incidence and economic burden of VTE following total joint arthroplasty (TJA) in the United States is unknown. The aim of this study was to examine this issue.